Amulets and Treatment With Al-Qur'an Verses (A Study of the Book of Tajul Muluk by Sheykh Ismail Al-Ashi) - Hadari; Ghalib Mattola; Nawas, Kamaludin Abu; Aderus , Andi (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2025)
The Qur'an can be used as a cure (Shifa') for various diseases, both physical and non-physical diseases and can be used as a mediator that has magical powers. Talisman in philosophical view, an influence over the human soul. This is done in an unnatural way that can affect a person's body. But the influences that arise, sometimes from the state of the spirit: such as the warmth that arises and the sense of excitement and joy, or sometimes and other psychic perceptions such as those arising from anxiety. The amulet in the process of its reaction seeks help from spiritual properties, the secrets of numbers, special qualities that manifest up to the fusion of the spirit with the substance of the body. Nowadays, the science of Qur'anic amulets is called magical letters. This science is used in the conventional sense which assumes that these amulets, have an inherent character or the secrets of the activities contained in the letters have a measure of calculation taken from the letters that contain the secrets contained in the creatures and nature. Medicine in the Kitab Taj al-Mulk is discussed separately. Some of the diseases and how to treat them are explained clearly and in great detail. Starting from the medicinal ingredients used, the dosage to the process of processing them to how to use the medicine is also explained in great detail. The Book of Tājul Muluk is the work of Sheikh Ismail bin Abdul Muttalib Al-Ashi, which was completed in 1249 in Mecca. The contents of this book include knowing the year and the moon, establishing a country, the conditions for building a house, knowing the good land, the relationship between husband and wife, ta'bir dreams, ta'bir earthquakes, ta'bir lunar eclipses, medicines taken from mujarrabat and so on. This book is not a compulsory book in Dayah or pondok, but it is studied by santri who have studied at a high level or they have become teachers. Kitab taj al-Mulk uses the method of clinical Sufism, which is part of the teaching of Sufism about the symbolism of the letters of the Qur'an used for treatment and divination. In Arabic, amulets are called at- tamā'im, which is an object deliberately made by a shaman, which is believed to contain magic and can reject all kinds of diseases for people who believe in it. Tangkal in Arabic is called ar-raqqī, which is defined as an object made by a shaman that is believed to be able to reject disease, evil spirits, and witchcraft.